1997
DOI: 10.1046/j.1365-2842.1997.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4-META adhesive on the bond strength of different metal framework designs and acrylic resins

Abstract: The effect of relining the 4-META adhesive resin onto metal alloy of a partial denture framework was tested. Seventy-two metal frameworks with three different retentive patterns were designed. Half of the specimens were treated with 4-META, the other group was left untreated. Thirty-six specimens were first divided into three groups in which 12 samples had different designs of retention, i.e. mesh, ring-shaped and flat plane. Then, each different retentive design was divided into two groups and in one group Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Mesh retention showed significantly higher mean separation forces than the lattice and smooth metal plate designs. This was consistent with Brown et al 3 and Canay et al, 33 who demonstrated that retentive mesh was more effective in retaining acrylic resin than the lattice design.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Mesh retention showed significantly higher mean separation forces than the lattice and smooth metal plate designs. This was consistent with Brown et al 3 and Canay et al, 33 who demonstrated that retentive mesh was more effective in retaining acrylic resin than the lattice design.…”
Section: Discussionsupporting
confidence: 89%
“…Cohesive bond failure in acrylic resin was observed more often among primed specimens, with the exception of mesh retentive specimens. Canay et al 33 also observed a cohesive shear bond fracture in the group treated with 4‐META and adhesive shear bond fracture in the untreated group.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations